6, 4–PP Photolyase Encoded by AtUVR3 is Localized in Nuclei, Chloroplasts and Mitochondria and its Expression is Down-Regulated by Light in a Photosynthesis-Dependent Manner. (24th October 2017) - Katarzyna Banaś, Agnieszka; Hermanowicz, Paweł; Sztatelman, Olga; Łabuz, Justyna; Aggarwal, Chhavi; Zgłobicki, Piotr; Jagiełło-Flasińska, Dominika; Strzałka, Wojciech
Abstract: Pyrimidine dimers are the most important DNA lesions induced by UVB irradiation. They can be repaired directly by photoreactivation or indirectly by the excision repair pathways. Photoreactivation is carried out by photolyases, enzymes which bind to the dimers and use the energy of blue light or UVA to split bonds between adjacent pyrimidines. Arabidopsis thaliana has three known photolyases: AtPHR1, AtCRY3 and AtUVR3. Little is known about the cellular localization and regulation of AtUVR3 expression. We have found that its transcript level is down-regulated by light (red, blue or white) in a photosynthesis-dependent manner. The down-regulatory effect of red light is absent in mature leaves of the phyB mutant, but present in leaves of phyAphyB. UVB irradiation does not increase AtUVR3 expression in leaves. Transiently expressed AtUVR3–green fluorescent protein (GFP) is found in the nuclei, chloroplasts and mitochondria of Nicotiana benthamiana epidermal cells. In the nucleoplasm, AtUVR3–GFP is distributed uniformly, while in the nucleolus it forms speckles. Truncated AtUVR3 and muteins were used to identify the sequences responsible for its subcellular localization. Mitochondrial and chloroplast localization of AtUVR3 is independent of its N-terminal sequence. Amino acids located at the C-terminal loop of the protein are involved in its transport into chloroplasts and its retention inside the nucleolus.